Implications of COVID-19 Infection on Medication Adherence with Chronic Therapies in Italy: A Proposed Observational Investigation by the Fail-to-Refill Project - Degli Esposti L; Buda S; Nappi C; Paoli D; Perrone V (Dove Medical Press, 2020)
Luca Degli Esposti,1 Stefano Buda,1 Carmela Nappi,1 Daniela Paoli,2 Valentina Perrone1 On behalf of Network Health-DB1CliCon S.r.l. – Health, Economics & Outcome Research, Ravenna, Italy; 2Health-DB, Ravenna, ItalyCorrespondence: Luca Degli EspostiCliCon S.r.l., Health, Economics & Outcomes Research, Via Salara, 36, Ravenna 48100, ItalyTel +39 (0)544 38393Fax +39 (0)544 212699Email luca.degliesposti@clicon.itAbstract: Poor medication adherence leads to worsening of clinical outcomes and increases healthcare costs, especially in the context of chronic conditions. The effects of new COVID-19 infection and the measures taken in response to the outbreak are further increasing the concerns about medication adherence. Patients with chronic diseases, many of whom are older adults, have been strongly recommended to stay at home and avoid social contacts even with family members, who often provide support for regular use of therapies. Moreover, the mobilization of health personnel to the frontline of the COVID-19 infection could limit access to healthcare services. Within the Health-DB project, the Fail-To-Refill monitoring system was designed to evaluate the lack of adherence to chronic therapies in Italian clinical practice settings. Considering the date and dose coverage of last prescription, all patients due to refill this prescription for a chronic therapy in the last month were identified, and it was verified if they had the refill. The proposed future analysis, based on the data linkage between the current administrative flows of the Italian Local Health Units involved, will be carried out on a monthly basis from the beginning of the infection, and the “post-Covid-19” results will be compared with “pre-COVID-19” results, calculated for the last three years for patients with chronic therapies. Preliminary data herein presented showed a trend of increased failed refill during the months of lockdown for lipid-lowering and biologic therapies. The pre-COVID-19 trend compared to that of post-COVID-19 in the next months will be useful to estimate the percentage of failure to refill truly related to COVID-19 and on the measures adopted. The identification of patients that do not refill their prescriptions allows healthcare professionals to put in place actions aimed to promptly correct the lack of adherence, thus reducing the associated negative outcomes.Keywords: chronic disease, real-world data, SARS-CoV-2, treatment adherence